Nanoskin (R) to treat full thickness skin wounds - Natsuaki Kaminagakura, Kryscia Leiko [UNESP]; Sato, Silvana Sue [UNESP]; Sugino, Patricia [UNESP]; Oliveira Veloso, Laryssa Kataki de [UNESP]; Santos, Daniela Carvalho dos [UNESP]; Padovani, Carlos Roberto [UNESP]; Basmaji, Pierre [UNESP]; Olyveira, Gabriel [UNESP]; Schellini, Silvana Artioli [UNESP] (Wiley-Blackwell, 2019)
This experimental study evaluated 40 guinea pigs that received Nanoskin (R). A full thickness skin rectangle measuring 2x4 cm was removed from the median dorsal region and the wound was covered by a 2X2 cm fragment of uncoated Nanoskin (R) graft (uncoated group) or Nanoskin (R) coated with gelatin (coated group) and sutured in the caudal region and a 2x2 cm fragment of autologous skin sutured in the cranial aspect of the surgical wound served a control. The animals were examined daily by ectoscopy and euthanized at 7, 30, 90 and 180 days postoperatively. Immediately after euthanasia, the operated area was shaved, documented with photos and removed, and prepared for morphological, morphometric and ultrastructural exam. It was found that the full thickness skin wound healed in a centripetal pattern. The healing process was similar between groups, with a more pronounced inflammatory reaction initially that gradually decreased over time. The conclusion is that the uncoated Nanoskin (R) or Nanoskin (R) coated with gelatin is a good material to treat full thickness skin wound. (c) 2018 Wiley Periodicals, Inc. J Biomed Mater Res B Part B: Appl Biomater, 2018. (c) 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 724-732, 2019.
Keywords: Nanoskin (R); nanocomposites; bacterial cellulose; Gluconacetobacter xylinum; full thickness skin graft